Overcoming Student Engagement Challenges: Effective Strategies for Creating Engaging Learning Environments - Santoso, Joko (Jurnal Ilmiah Kanderang Tingang, 2023)
In today’s higher education, student involvement in the learning environment is a major focus. This paper investigates the problems students face in terms of academic and social engagement, and analyzes effective strategies for making the learning environment engaging. Low motivation, lack of significant social interaction, and feeling less connected to lessons are some of the problems that hinder student engagement. To find out how students see this problem, this research uses a literature study or literature study method. The research results show that several strategies can increase student engagement. These strategies include using interactive educational technology, making the curriculum relevant to the real world, and encouraging collaboration and social interaction inside and outside the classroom. In this context, the important role of educators in facilitating inspiring learning experiences is also noted.